2006
DOI: 10.1158/1055-9965.epi-06-0272
|View full text |Cite
|
Sign up to set email alerts
|

PGR+331 A/G and Increased Risk of Epithelial Ovarian Cancer

Abstract: Childbearing and use of oral contraceptives are known to lower the risk of ovarian cancer, and it has been suggested that progesterone or progestin exposures play a role in these associations. The effects of progesterone may be mediated in part through the progesterone receptor, which exists in two functionally distinct protein isoforms, hPR-A and hPR-B. It is known that individuals carrying the A allele of the progesterone receptor gene (PGR) polymorphism, +331 A/G (rs10895068), have greater production of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 10 publications
2
47
1
Order By: Relevance
“…This association was particularly strong among clear cell/ endometrioid subtypes. However, Risch et al (2006) observed an increased risk of ovarian cancer associated with this SNP.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…This association was particularly strong among clear cell/ endometrioid subtypes. However, Risch et al (2006) observed an increased risk of ovarian cancer associated with this SNP.…”
mentioning
confidence: 86%
“…The participating groups for this PGR study are the Australian Cancer Study, (Merritt et al, 2008) the Australian Ovarian Cancer Study (Merritt et al, 2008), the Connecticut Ovary Study (CONN) (Risch et al, 2006), the Family Registry for Ovarian Cancer Study (Auranen et al, 2005;Song et al, 2006), the Hormones and Ovarian Cancer Prediction Study, the Danish Malignant Ovarian Cancer Study (MALOVA) (Auranen et al, 2005;Song et al, 2006), the Mayo Clinic Ovarian Cancer Case -Control Study (Sellers et al, 2005), the North Carolina Ovarian Cancer Study (Berchuck et al, 2004), the New England-based Case -Control Study (NECC) (Terry et al, 2005), the Polish Ovarian Cancer Study (POCS) (García-Closas et al, 2007), the UK SEARCH Ovarian Cancer Study (SEARCH) (Auranen et al, 2005;Song et al, 2006) and the USC/Los Angeles County Case -Control Studies of Ovarian Cancer (USC) (Pearce et al, 2005). Details of these studies have been published previously (Gayther et al, 2007); Table 1 shows the basic information for each study.…”
Section: Study Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some case-control studies have suggested that PROGINS is protective against BC [2] but a risk-factor for OC [14,15,17], whereas the +331A allele appeared to be a risk-factor both for BC [19] and for OC [15,21]. Other authors, however, did not find any association [13,17,[22][23][24][25][26]28].…”
Section: Discussionmentioning
confidence: 99%
“…In case of the +331G/A promoter polymorphism [13], the rare allele +331A (with a frequency of 0.06-0.08 among Caucasians) increases the relative PRB/PRA expression compared to +331G. Both polymorphisms have been shown to modify the risk for breast [2,[17][18][19] and OC [14,15,17,20,21] in several case-control studies. However these associations were not confirmed by other studies [13,17,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%